Interrelation between Handwashing and the Severity of COVID-19: A non-representative cross-sectional study - Nabila Putri Firdalina; Riry Ambarsarie; Utari Hartati Suryani; Dessy Triana; Nikki Aldi Massardi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Corona Virus Disease 2019 (COVID-19) pandemic remains a global issue, including in Indonesia. Handwashing using soap can reduce the viral load of the SARS-CoV-2 virus and prevent coinfection, which can worsen symptoms in COVID-19 patients. This study aims to determine the relationship between knowledge, attitudes, and handwashing behavior to the severity of COVID-19. Research using a cross-sectional and retrospective approach was conducted from July to December 2020 in Bengkulu Province. About 107 respondents had been confirmed positive for Covid-19 with the rt-PCR test, aged 17-60 years, and were willing to participate. Knowledge, attitudes, and behaviors were assessed using validated questionnaires and data on the severity of disease obtained from epidemiological forms. The collected data were then analyzed using chi-square statistical tests. 107 respondents had already filled in the questionnaires. The Chi-square test showed no significant association between knowledge (p 0.081), attitude (p 0.216), and behavior (p 0.136) of handwashing to the severity of COVID-19. A good level of knowledge, attitudes and behaviors about handwashing using soap did not adequately affect the severity of covid-19 patients. The good level of knowledge, attitude, and practice of HWUS were not significant enough to affect the severity of the COVID-19 disease.